Real life learning. - Makhubela-Nkondo, O.N. (Nursing Update, 2011)
In the first of a series of memoirs on a prolific sabbatical leave spent at the North West University, Mafikent Campus, First Vice-President, DENOSA professional matters, O.N. Makhubela-Nkondo (RN. RM. RCHN. RNE. M & D, University of South Africa), speaks about the programme offered at the North West University to refine nurses' psycho-motor skills for clinical excellence.